Conservation and Management of Mangrove Ecosystems in Supporting Ecotourism Development in Marisa District - Ramla Hartini Melo; Fazriwan Mohi; Nurdin Mohamad; Syarifah Fatimah Setiasih Niode; David Omanayi Johnson (Geosfera: Jurnal Penelitian Geografi, 2026)
Mangrove ecosystems provide critical ecological services, support coastal livelihoods, and contribute significantly to climate change mitigation through their blue carbon storage capacity. Despite their importance, many mangrove areas in Indonesia continue to face increasing pressures from land-use conversion, resource exploitation, environmental degradation, and climate-related threats. Community-based ecotourism has emerged as a promising strategy for balancing ecosystem conservation and local economic development; however, effective management requires a comprehensive understanding of internal capacities and external challenges affecting mangrove sustainability. This study aims to evaluate the strategic potential of mangrove ecosystem conservation and management in Pohuwato Regency, Indonesia, to support sustainable community-based ecotourism development. Data were collected through field observations, questionnaires, and stakeholder assessments and analyzed using SWOT (Strengths, Weaknesses, Opportunities, and Threats) supported by IFAS and EFAS matrices. The results revealed an IFAS score of 2.45 and an EFAS score of 2.53, producing strategic coordinates of X = 1.05 and Y = 0.61. These values position the study area within Quadrant I of the SWOT matrix, indicating a strong capacity to pursue an aggressive development strategy by leveraging existing strengths and opportunities. High ecotourism potential, mangrove biodiversity, institutional collaboration opportunities, and conservation funding availability emerged as the most influential factors supporting future development. The study highlights that strengthening community participation, enhancing ecotourism infrastructure, and promoting collaborative governance are essential for achieving long-term coastal sustainability. These findings contribute to the growing discourse on integrating mangrove conservation and ecotourism as a pathway toward resilient coastal development and sustainable blue economy initiatives in tropical regions.